HUBUNGAN HS-CRP DENGAN KADAR TRIGLISERIDA PASIEN OBESITAS DI RUMAH SAKIT SILOAM BALI - Anak Agung Ayu Eka Cahyani; I Putu Yogi Bhyomantara; Putu Ayu Parwati (Yakpermas Press, 2024)
Obesity is excessive accumulation of fat due to an imbalance between energy intake and energy expenditure for a long time. Someone is categorized as obese if their body mass index is more than 25. Obesity triggers various diseases such as coronary heart disease, stroke, cancer and diabetes. Obesity is also one of the factors that affect the increase of triglyceride levels. Beside of increased triglyceride levels, obese patients there is also get increase in hs-CRP levels above normal limits. This study aims to determine the relationship between hs-CRP and triglycerides in obese respondents. This type of research used is correlational. The study was conducted at Siloam Hospital Bali from February to March 2023. The sample in this research was 30 obese respondents who were examined for hs-CRP and triglyceride levels. The results showed that 13 people (43,3%) were in the high category and 1 person (3,3%) was in the very high category. Hs-CRP levels in the respondents were 25 people (83%) with normal hs-CRP levels or less than 5 mg/l and 5 people (17%) with hs-CRP levels of 5 mg/l. Based on the results of the correlation test, it was found that the p-value was 0,505 which indicated a p-value greater than 0,05, meaning that there was no correlation between hs-CRP levels and triglyceride levels. This is probably because the respondent has not carried out strenuous activities, no inflammation and has received treatment related to obesity status.